Data note for cross-country data on social cohesion and Covid-19 - Irene van Staveren; Jimena Pacheco-Miranda; Sanchita Bakshi (Journal of Applied Economics, 2024)
This Data Note is a brief explanation of a dataset compiled for a study on the relationship between social cohesion and Covid-19. The innovative variable in this cross-country dataset is social cohesion, which appears as a consolidated index and as two sub-indices on, respectively, the interpersonal dimension and the intergroup dimension of social cohesion. This variable is available for 187 countries. We discuss the underlying indicators, provide their sources and a link to the full dataset. In addition, we provide information about the online, freely available database called Indices of Social Development of which the social cohesion sub-indices make part. With our explanation of the theoretical background, substance of the indicators, and construction of the three social cohesion indices, we hope to inspire researchers to use them in their own cross-country research.
Keywords: 330; Covid-19; Dataset; Social Cohesion